The time machine - Wells, H. G. (Hubert George) (New York : Scholastic, 2002)
The Time Traveler of this novella tests his time machine with a leap forward to the year 802,701 A.D., to find that evolution has produced two very different post-human races - the peaceful and childlike fruit-eating Eloi and the Morlocks - pale, darkness-dwelling troglodites who operate the underground machinery that makes this seeming paradise possible.
Keywords: Time travel -- Fiction; Science fiction